Хроники миграционных событий в Украине до и после распада СССР - Прибыткова, И. (Социология: теория, методы, маркетинг, 2009)
Robert Park, the founder of the Chicago School of Sociology, held the migrations, revolutions and wars to be phenomena of the same nature so far as they break the natural course of human history. The migratory processes bear inevitably the marks of their time. Their nature and trends reflect productive, distributive, public and political relations immanent to the social system which has given rise to them. August 1991 and the following disintegration of the USSR and formation of the Commonwealth of Independent States became the turning-point in migration processes running on the boundless spaciousness of the collapsed empire. Migration situation assumed the new in essence characteristics, migratory priorities have changed. Transformation of all directions, structures and intensity of contemporary migratory movements is a new in the main phenomena and corroborates the truth of Robert Park’s postulates. The changes in migratory flows in Ukraine before and after the collapse of the Soviet Union are discussed in the article. The author has scrutinized the dominants of migratory situation in the different periods of migration history in Ukraine. It has been analyzed the state migration policy and its economical, social and ethnic con se quences. The parameters of migration potential in Ukraine are given as well. The author comes to the conclusion that a new migratory balance is achieved in Ukraine. There is noted also a dual character of migration situation in the conditions of global financial and economic crisis. It is complicated to predict today its future design. Time will show.